Analyzing user opinions on content and social media apps to online marketing: Evidence from Albania - Vukatana, Kreshnik; Mulla, Gjergji; Liu, Ran; Mitre, Xhulio (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study investigates the relationship between online marketing and social media apps (Facebook, Instagram, Snapchat, and LinkedIn) or content apps (YouTube and Netflix), focusing on Albanian markets. Based on the analysis of 525 Albanian social media users from different age groups, the findings illustrate that 90% of the respondents prefer to use a smartphone rather than a personal computer in their daily life. Except for LinkedIn and Facebook, all social media apps had higher usage rates among the younger demographic, according to data analysis. The most popular app is Facebook. Based on age-based differentiation strategies, our data support the findings. Every app can help businesses reach the Youth category (aged 14 to 24), but social networking apps and YouTube should be the main priorities. Adults in the target audience in the 25–45 age range can be found primarily on Facebook, Instagram, and YouTube, while people over 45 can be found primarily on Facebook. Specifically, companies investing in online marketing can use Instagram and YouTube, which are more popular among younger social media users, while older users prefer Facebook and LinkedIn. Meanwhile, it would be better not to use in-app purchase strategies for companies that intend to invest through their apps.